2019
DOI: 10.2147/dmso.s228654
|View full text |Cite
|
Sign up to set email alerts
|

<p>lncRNA GAS5/miR-452-5p Reduces Oxidative Stress and Pyroptosis of High-Glucose-Stimulated Renal Tubular Cells</p>

Abstract: BackgroundDiabetic nephropathy (DN) is the leading cause of end-stage renal failure worldwide. lncRNAs are demonstrated to improve the DN by changing the expression of miRNAs. This study was aimed to investigate the effect of lncRNA GAS5/miR-452-5p on the inflammation, oxidative stress and pyroptosis of high-glucose-induced renal tubular cells.MethodsHK-2 cells were induced by HG to simulate DN cells. RT-qPCR analysis confirmed the transfection effects and detected the expression of GAS5, NLRP3, caspase1, IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 29 publications
(23 reference statements)
3
72
0
Order By: Relevance
“…Therefore, we supposed that GAS regulated the expression of INSR, PIK3R1 and IRS1 through competitively interacting miR-29a-3p, miR-96-3p, and miR-208a-3p, but we cannot exclude other mechanisms play a role in this regulation, such as epigenetic mechanism (Sun et al, 2017). MiR-452-5p and miR-221-3p are two valid targets of GAS5 in renal tubular cells and mesangial cells, respectively, and both of them are involved in diabetic nephropathy (Ge et al, 2019;Xie et al, 2019). However, the levels of miR-452-5p and miR-221-3p were comparable between high GAS5 group and low GAS5 group.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, we supposed that GAS regulated the expression of INSR, PIK3R1 and IRS1 through competitively interacting miR-29a-3p, miR-96-3p, and miR-208a-3p, but we cannot exclude other mechanisms play a role in this regulation, such as epigenetic mechanism (Sun et al, 2017). MiR-452-5p and miR-221-3p are two valid targets of GAS5 in renal tubular cells and mesangial cells, respectively, and both of them are involved in diabetic nephropathy (Ge et al, 2019;Xie et al, 2019). However, the levels of miR-452-5p and miR-221-3p were comparable between high GAS5 group and low GAS5 group.…”
Section: Discussionmentioning
confidence: 93%
“…LncRNA, as a competitive endogenous RNA (ceRNA), binds to miRNA and acts as a miRNA sponge, thereby reducing the activity of miRNA and indirectly up-regulating the expression of miRNA-related target genes (Goustin et al, 2019). It has been reported that GAS5 targets to miR-452-5p and miR-221-3p in renal tubular cells and mesangial cells, which are involved in diabetic nephropathy (Ge et al, 2019;Xie et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the pyroptosis pathway, GSDMD is cleaved by inflammatory caspases at an aspartate site within the linking loop, thereby generating the self-inhibited group GSDMD-C-terminal (GSDMD-CT) and the active group GSDMD-N-terminal (GSDMD-NT) [ 32 , 33 ]. Inhibitory binding between GSDMD-NT and GSDMD-CT leads to the inactivity of GSDMD.…”
Section: Biology Of Pyroptosismentioning
confidence: 99%
“…Meanwhile, tubular cell injury has something to do with the role of GSDMD-NT in promoting pyroptosis. After transfecting the HG-induced renal tubular epithelial cells (HK-2 cells) with miRNA-452-5p inhibitor, they detected the marked downregulation of the expressions of NLRP3, caspase-1 and GSDMD-NT [ 32 ]. However, the concrete effect of GSDMD-NT on cell pore formation in tubular cells has yet to be tested.…”
Section: Biology Of Pyroptosismentioning
confidence: 99%
See 1 more Smart Citation